Montagem e modelagem de um grupo gerador síncrono-turbina hidráulica para seu estudo e operação em micro centrais hidroelétricas para pequenos sistemas isolados - Saavedra, Álvaro Christian Montaño (2011)
This work presents the assembly and modeling of a plant constituted by one turbine and one synchronous generator to function as a part of a Micro Hydroelectric Plant (MHP) for small isolated systems. Once the assembly of the plant at the laboratory was constructed, has started the developing of an empirical model of the process in the form of reaction curves, obtained by the use of the step response technique that allowed the approximation of the main variables involved in a first order with dead time model. After obtaining the transfer functions of the plant, a PID controller was designed in order to maintain the output voltage of the generator on an appropriate reference value for electrical distribution in the network of the isolated electric system. With the purpose of validate the simulation results, curves of response were obtained from the real system in the laboratory and were compared to both responses,giving a satisfactory and very similar result. These results will functionate as a basis for further studies in the areas of speed control (or charge controller) and system stability, among others, in the field of MHPs for small isolated systems